UPAH MENGUPAH PERTANIAN DALAM TINJAUAN FIQH MUAMALAH (Studi di Nagari Bukit Kandung Kecamatan X Koto Diatas Kabupaten Solok) - Susanti Krismon; Syukri Iska (Jurnal Integrasi Ilmu Syariah (Jisrah), 2021)
This article discusses the implementation of wages in agriculture in Nagari Bukit Kandung Subdistrict X Koto Atas, Solok Regency in a review of muamalah fiqh. The type of research is field research (field research). The data sources consist of primary data sources, namely from farmers and farm laborers who were carried out to 8 people and 4 farm workers, while the secondary data were obtained from documents in the form of the Bukit Kandung Nagari Profile that were related to this research, which could provide information or data. Addition to strengthen the primary data. Data collection techniques that the author uses are observation, interviews and documentation. The data processing that the author uses is qualitative. Based on the results of this study, the implementation of wages in agriculture carried out in Nagari Bukit Kandung District X Koto Diatas Solok Regency is farm laborers who ask for their wages to be given in advance before they carry out their work without an agreement to give their wages at the beginning. Because farm laborers ask for their wages to be given at the beginning, many farm workers work not as expected by farmers and there are also farm workers who are not on time to do the work that should be done. According to the muamalah fiqh review, the implementation of wages in agriculture in Nagari Bukit Kandung is not allowed because there is an element of gharar in the contract and there are parties who are disadvantaged in the contract, namely the owner of the fields.